THE MINDFULNESS TECHNIQUE FOR TREATMENT OF OCD: A SYSTEMATIC REVIEW - dos Santos Almeida, Rute; Medeiros de Oliveira, Olívia (Health and Society, 2023)
Obsessive Compulsive Disorder is one of the most disabling mental disorders in the world and there are different interventions in the treatment strategy for obsessive compulsive disorder. A recent technique that has been gaining ground within positive psychology is Mindfulness, this technique has shown promising results and is being used as a new resource for adherence to the treatment of OCD symptoms. The aim of this study was to perform a systematic review of the literature to verify the therapeutic efficacy of mindfulness-based interventions for the treatment of patients with obsessive-compulsive disorder. The study was carried out through a systematic review of the literature in the following databases: Pubmed, Psycinfo, BVS and Web of Science. The keywords used were searched in the Descriptors in Health Sciences (DecS) terminology banks. These were complemented by keywords found in reference articles on the subject. The following string was used: “mindfulness” AND “obsessive compulsive disorder” OR “OCD”. Initially, a total of 320 articles were found, after applying the inclusion and exclusion criteria, 19 articles entered this review. Mindfulness-based interventions have emerged as an important therapeutic tool. Research on the subject points to its role in reducing the symptoms of obsessive-compulsive disorder and increasing quality of life. The results of different interventions point to the potential of mindfulness-based programs and the benefits of their application in individuals with obsessive-compulsive disorder.